The Southern Hemisphere Blocking Index Revisited - Yuchechen, Adrian Enrique (2022)
An updated climatology for the occurrence of blockings in the Southern Hemisphere (SH) using daily reanalysis data from 1948–2021 is presented. Geopotential height (Formula presented.) at 500 hPa was the working variable. The blocking index (BI) was defined for every 2.5° of longitude whenever (Formula presented.). The results were organized in longitudinal bands of a width of 10° in order to compare them with previous findings. The primary region for the occurrence of blockings was located around the date line, with a secondary region in southern South America (SSA) and its vicinities, with a third-rank region situated in southern Africa and its surroundings. The results were also stratified by the intensity and duration (persistence) of the events, and the annual and seasonal differences were discussed. Additionally, three different areas were defined to study the distribution of the blockings therein, with the Pacific region (110° E–80° W) having the maximum intensities and longest durations. Linear trends were estimated for the annual and the seasonal time series of the BI and for the number of episodes. On an annual basis, more frequent and the strongest events are expected at 180° E and their surroundings in the future. An alternative BI, using radiosonde data, was built for SSA at 58.50° W. The time evolution of this index was in general agreement with the one estimated from the reanalysis data at some longitudes.